Implementación de un programa ergonomico para disminuir los riesgos asociados a trastornos musculo-esqueleticos en la empresa constructora sga s.r.l., 2018. - La Madrid Guanilo, Marx Lenin (2019)
The present research work, the objective of the implementation of an ergonomic program to reduce the risks associated with skeletal muscle disorders in the construction company SGA S.R.L, 2018. The methodologies RULA (Rapid assessment of the upper extremities) and REBA (Rapid assessment of the whole body) are used to perform the postural evaluation of activities that involve greater ergonomic risk within the area of operations of the company SGA S.R.L. A total of nine activities considered for the analysis were selected: manual excavation, hoisting with pulley, hoisting with winch, formwork and stripping, scaffolding assembly, electrical wiring, electric welding, cutting and grinding and oxyacetylene operations. The postural evaluation is done to determine the areas of the body more than it is used for the results an ergonomic program is offered to reduce the unfavorable ergonomic postures, in which a series of exercises of stretching and muscular strengthening of the areas of the body is included more committed as the neck, trunk, arms and forearms. Finally, the economic analysis carried out showed favorable values for the economic indicators, obtaining a net real value (NPV) of $ 1,427.06 and an internal rate of return (IRR) of 15.53%; This indicates that the proposal of the ergonomic plan is profitable and therefore the implementation is recommended.